2020
DOI: 10.15632/jtam-pl/117813
|View full text |Cite
|
Sign up to set email alerts
|

Moving semi-infinite mode-III crack inside the semi-infinite elastic media

Abstract: The problem of a semi-infinite moving mode-III crack inside a semi-infinite isotropic half--space is considered. The crack is located between a semi-infinite elastic medium and a layer whose distance from the surface to crack depth is h. Initially, Fourier transformation and inverse Fourier transformation are applied to transfer the governing boundary value problem to the well-known Wiener-Hopf equation. The purpose of this problem is to obtain the analytical solution of Stress Intensity Factor (SIF) and Crack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…1 (the black one) is for without magnetoelasticity in the Figures 9 and 10 for purely orthotropic and isotropic medium respectively. The nature of these two curve shows the total agreement to the Figures 3 and 4 of the study of karan et al [20] and Figures 3 and 4a,b of findings of Mondal [19]. Although the expression of SIF is deduce in special case section 6 (see case-II and case-III) for orthotropic and isotropic medium without magnetoelasticity.…”
Section: Numerical Results and Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…1 (the black one) is for without magnetoelasticity in the Figures 9 and 10 for purely orthotropic and isotropic medium respectively. The nature of these two curve shows the total agreement to the Figures 3 and 4 of the study of karan et al [20] and Figures 3 and 4a,b of findings of Mondal [19]. Although the expression of SIF is deduce in special case section 6 (see case-II and case-III) for orthotropic and isotropic medium without magnetoelasticity.…”
Section: Numerical Results and Discussionsupporting
confidence: 87%
“…Singh et al [18] studied moving sem-infinite crack in sandwiched orthotropic strip. Mandal [19] studied the mode-III moving crack problem for isotropic medium and then it was explored by Karan et al [20] for material orthotropy. Considering the semi-infinite moving crack at interface of two orthotropic layer, Trivedi and Das [21] studied for anti-plane shear wave.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [31], it is shown that the steady-state stress intensity factor for the problem described above is…”
Section: Stress Intensity Factormentioning
confidence: 99%
“…The analytical solution for the SIF by Mandal [31] is based on the assumption of a quasi-stationary problem. This implies certain constraints on the geometry of the domain and the prescribed boundary conditions.…”
Section: Validationmentioning
confidence: 99%